Double valve infective endocarditis due to Capnocytophaga canimorsus. (2022) - Harrigan, Amye; Murnaghan, Kyle; Robbins, Mark
Abstract: Infective endocarditis caused by Capnocytophaga canimorsus, a commensal organism commonly found in dog saliva, is uncommon. We describe a case of a 76-year-old male with native aortic and mitral valve endocarditis with ventricular-atrial fistulization due to Capnocytophaga canimorsus . He was successfully treated with intravenous antimicrobials and surgery. Capnocytophaga canimorsus should be considered as a cause of infective endocarditis in patients with negative blood cultures, in asplenic patients, and in those with appropriate exposures.